LGG-50. Human induced pluripotent stem cell engineering establishes a humanized mouse platform for pediatric low-grade glioma modeling. (3rd June 2022) - Anastasaki, Corina; Chatterjee, Jit; Cobb, Olivia; Scheaffer, Suzanne; Sanapala, Shilpa; Costa, Amanda; Wilson, Anna; Garbow, Joel; Rodriguez, Fausto; Gutmann, David
Abstract: A major obstacle to identifying improved treatments for pediatric low-grade brain tumors (gliomas) is the inability to reproducibly generate human xenografts. To surmount this barrier, we leveraged human induced pluripotent stem cell (hiPSC) engineering to generate low-grade glioma (LGG) lesions representing the two most common pediatric pilocytic astrocytoma-associated molecular alterations, NF1 loss and KIAA1549:BRAF fusion. Using hiPSCs, we identified the susceptible cells of origin for these tumors, and demonstrated that the resulting tumors retain LGG histologic features for at least 6 months in vivo. Finally, this platform enabled the successful long-term growth of patient-derived pLGGs in vivo . Taken together, these avatars establish tractable experimental humanized platforms to elucidate the pathogenesis of childhood brain tumors.